Comparison of emergency department utilization trends between the COVID-19 pandemic and control period. Issue 32 (13th August 2021) - Kang, Soo; Ahn, Tae Kyu; Seo, Young Ho; Suh, Young Ju; Paik, Jin Hui
Abstract : Abstract: Infectious disease pandemics has a great impact on the use of medical facilities. The purpose of this study was to analyze the effects of coronavirus disease 2019 (COVID-19) on the use of emergency medical facilities in the Republic of Korea. This single-center, retrospective observational study was conducted in a tertiary teaching hospital located in Incheon Metropolitan City, Republic of Korea. We set the pandemic period as February 19, 2020 to April 18, 2020, and the control period was set to the same period in 2018 and 2019. All consecutive patients who visited the emergency department (ED) during the study period were included. Patients were divided into 3 groups according to age (pediatric patients, younger adult patients and older adult patients). The total number, demographics, clinical data, and diagnostic codes of ED patients were analyzed. The total number of ED patients in the pandemic period was lower than that in the control period, which was particularly pronounced for pediatric patients. The proportion of patients who used the 119 ambulances increased in all 3 groups ( P = .002, P < .001, and P = .001), whereas the proportion of patients who visited on foot was decreased ( P = .006, P < .001, and P = .027). In terms of diagnostic codes, a significant decrease was observed in the proportion of certain infectious or parasitic diseases (A00-B99), and respiratory diseases (J00-J99) in the pediatric and younger adult patient groups ( P < .001 and P < .001, respectively). The COVID-19 pandemic reduced the number of ED patients; however, the proportion of patients using ambulances increased. In particular, the proportion of patients with diagnostic codes for infectious and respiratory diseases significantly decreased during the pandemic period.